Catalytic cracking catalyst, process for its preparation and use

CN118847191BActive Publication Date: 2026-10-16CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202310478563.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-28
Publication Date
2026-10-16
Estimated Expiration
2043-04-28

AI Technical Summary

Technical Problem

对于污染金属镍、铁而言,其迁移性差,主要在催化剂表面2-3μm处富集,而常规催化剂中的抗金属组元一般均匀分布在催化剂颗粒中,导致其与表面金属的接触效率大大下降

Benefits of technology

[0020] The catalyst preparation method provided by this invention employs three specific binder precursors in combination and effectively ensures the catalyst's wear index by controlling the particle size of the first microspheres. Furthermore, through specific steps, the catalyst exhibits excellent resistance to metal contamination. The preparation method of this invention has wide applicability and is suitable for preparing catalysts containing different molecular sieves. The catalyst prepared by the method of this invention, when used in heavy oil catalytic cracking, exhibits high heavy oil conversion and high liquid yield. The catalyst provided by this invention demonstrates excellent resistance to metal contamination, achieving high total liquid product yield and high gasoline yield even under metal contamination conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118847191B_ABST
    Figure CN118847191B_ABST
Patent Text Reader

Abstract

The application relates to the field of catalytic cracking catalysts, and discloses a catalytic cracking catalyst as well as a preparation method and application thereof. The catalytic cracking catalyst comprises a molecular sieve, clay and a composite binder; wherein the composite binder comprises a first binder, a second binder and a third binder; the first binder is obtained by calcining pseudo-boehmite with a crystal grain size of 2-5 nm, the second binder is obtained by calcining pseudo-boehmite with a crystal grain size of 10-30 nm, and the third binder is obtained by calcining magnesium-aluminum sol with a viscosity of not less than 500 mPa.s. The catalytic cracking catalyst has excellent metal pollution resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of catalytic cracking catalysts, specifically to a catalytic cracking catalyst, its preparation method, and its application. Background Technology

[0002] With the increasing scarcity of oil resources and the continuous rise in crude oil prices, major refineries are reducing costs and maximizing profits by deeply processing heavy oil and using inferior oil. Currently, catalytic cracking is an important means of heavy oil processing.

[0003] However, low-quality crude oil generally has a high content of heavy metals (such as vanadium, nickel, and iron). Especially in recent years, due to the increasing weight and deterioration of feedstock oils and the processing of opportunistic crude oils, metal poisoning of catalytic cracking catalysts has become increasingly common. Numerous studies have shown that once metals such as iron and nickel deposit on the surface, they are difficult to migrate, causing sintering on the catalyst surface and forming a dense layer 2-3 μm thick. This layer blocks the pores through which reactants enter the catalyst and products diffuse, thus worsening product distribution.

[0004] In US3944482, the catalyst matrix has an average pore size ≥9 nm, which reduces the dispersibility of heavy metal nickel and enhances the catalyst's nickel resistance. US4750988 discloses a vanadium scavenger using MgO as the active vanadium-capturing material (mass fraction 5%–35%), with a specific surface area of ​​100–500 nm. 2 The vanadium scavenger, in a 10%–15% proportion in the system, uses Al₂O₃ as the support, with n(MgO):n(Al₂O₃) = (0.01–2):1, the optimal range being (0.05–0.5):1. The mixture may also contain 0.1%–2% vanadium oxide. This vanadium scavenger is prepared by impregnating magnesium compounds onto Al₂O₃, followed by drying and calcination. It can improve the conversion rate and selectivity of the feedstock, thereby increasing gasoline yield. CN1334315A describes a method for preparing a heavy metal-resistant FCC catalyst by adding 1–25 mg% of a metal-catching component, such as rare earth oxides like rare earth oxalate. This catalyst exhibits excellent heavy metal resistance and is suitable for cracking heavy oils with high Ni and V content.

[0005] In general, currently reported industrial-grade anti-metal catalytic cracking catalysts mainly consist of active components such as alumina, rare earth elements, and alkaline earth metals. These active components react with metals to form more stable compounds, achieving anti-nickel and vanadium effects. For contaminating metals like nickel and iron, their migration is poor, and they are mainly enriched at a depth of 2-3 μm on the catalyst surface. However, anti-metal components in conventional catalysts are generally uniformly distributed within the catalyst particles, leading to a significant decrease in their contact efficiency with the surface metals. Some methods, such as coating, introduce anti-metal components onto the catalyst surface, as described in CN113492014A. However, both spraying and rinsing methods result in the loss of most of the anti-metal components during the washing process, causing resource waste.

[0006] Therefore, it is essential to prepare a catalyst with good resistance to metal contamination. Summary of the Invention

[0007] The purpose of this invention is to overcome the problems existing in the prior art and provide a catalytic cracking catalyst, its preparation method, and its application. The catalytic cracking catalyst of this invention has excellent resistance to metal contamination.

[0008] To achieve the above objectives, the present invention provides a catalytic cracking catalyst, the catalyst comprising a molecular sieve, clay, and a composite binder;

[0009] The composite binder includes a first binder, a second binder, and a third binder; the first binder is obtained by calcining pseudoboehmite with a grain size of 2-5 nm, the second binder is obtained by calcining pseudoboehmite with a grain size of 10-30 nm, and the third binder is obtained by calcining magnesium aluminum sol with a viscosity of not less than 500 mPa·s.

[0010] Preferably, the weight ratio of the first adhesive to the second adhesive is 1-5:1, more preferably 1-3:1.

[0011] Preferably, the weight ratio of the first adhesive and the second adhesive to the third adhesive is 1-10:1, more preferably 1-6:1.

[0012] A second aspect of the present invention provides a method for preparing a catalytic cracking catalyst, the method comprising the following steps:

[0013] (1) The first adhesive precursor is first sol-gelled;

[0014] (2) The material, molecular sieve and clay obtained in step (1) are mixed for the first time to obtain the first slurry, and then spray-dried for the first time to obtain the first microsphere particles with an average particle size of no more than 30 μm.

[0015] (3) The second adhesive precursor is subjected to a second sol-gel process;

[0016] (4) The material obtained in step (3), the first microsphere particles and the third binder precursor are mixed for the second time to obtain the second slurry, and then spray-dried for the second time to obtain the catalytic cracking catalyst.

[0017] Wherein, the first binder precursor is boehmite with a grain size of 2-5 nm, the second binder precursor is boehmite with a grain size of 10-30 nm, and the third binder precursor is magnesium aluminum sol with a viscosity of not less than 500 mPa·s.

[0018] Preferably, the viscosity of the material obtained in step (1) is not less than 20000 mPa·s.

[0019] Preferably, the viscosity of the material obtained in step (3) is not greater than 200 mPa·s.

[0020] The catalyst preparation method provided by this invention employs three specific binder precursors in combination and effectively ensures the catalyst's wear index by controlling the particle size of the first microspheres. Furthermore, through specific steps, the catalyst exhibits excellent resistance to metal contamination. The preparation method of this invention has wide applicability and is suitable for preparing catalysts containing different molecular sieves. The catalyst prepared by the method of this invention, when used in heavy oil catalytic cracking, exhibits high heavy oil conversion and high liquid yield. The catalyst provided by this invention demonstrates excellent resistance to metal contamination, achieving high total liquid product yield and high gasoline yield even under metal contamination conditions.

[0021] The third aspect of this invention provides the application of the catalytic cracking catalyst described in the first aspect or the catalytic cracking catalyst prepared by the method described in the second aspect in the catalytic cracking of feedstock oil.

[0022] The beneficial effects of the present invention through the above technical solution include:

[0023] The catalyst provided by this invention is used for heavy oil catalytic cracking and exhibits high heavy oil conversion rate and high total liquid product yield. As shown in the examples, the highest heavy oil conversion rate can reach 67.83 wt%, and the highest total liquid product yield can reach 78.69 wt%.

[0024] The catalyst provided by this invention exhibits excellent resistance to metal contamination, achieving high total liquid product yield and high gasoline yield even in the presence of metal contamination. As shown in the examples, the gasoline yield can reach up to 45.03 wt%. Preferably, the catalyst provided by this invention has a low abrasion index, which enhances its fluidization performance and high-temperature abrasion resistance, thereby increasing catalyst life and enabling long-term operation. Attached Figure Description

[0025] Figure 1 This is an EDS diagram of the catalyst prepared in Example 1 of the present invention. Detailed Implementation

[0026] The endpoints and any values ​​of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.

[0027] In one aspect, the present invention provides a catalytic cracking catalyst, the catalyst comprising a molecular sieve, clay, and a composite binder;

[0028] The composite binder includes a first binder, a second binder, and a third binder; the first binder is obtained by calcining pseudoboehmite with a grain size of 2-5 nm, the second binder is obtained by calcining pseudoboehmite with a grain size of 10-30 nm, and the third binder is obtained by calcining magnesium aluminum sol with a viscosity of not less than 500 mPa·s.

[0029] The catalytic cracking catalyst provided by this invention employs the synergistic effect of a small-grained first binder, a large-grained second binder, and a third binder with a specific viscosity, which is beneficial to improving the catalyst's resistance to metal contamination and reducing the catalyst's wear index.

[0030] According to the present invention, preferably, the first binder is obtained by calcining pseudoboehmite with a grain size of 2-5 nm, the second binder is obtained by calcining pseudoboehmite with a grain size of 10-20 nm, and the third binder is obtained by calcining magnesium aluminum sol with a viscosity of 500-2000 mPa·s.

[0031] The present invention does not particularly limit the calcination conditions. For example, the calcination conditions for the first binder can be the first and second calcination conditions in the preparation method described below. The calcination conditions for the second binder can be the second calcination conditions in the preparation method described below. The calcination conditions for the third binder can be the second calcination conditions in the preparation method described below.

[0032] The grain size of the pseudoboehmite described in this invention was measured by X-ray diffraction (XRD).

[0033] The viscosity of the magnesium-aluminum sol described in this invention was measured using a viscometer.

[0034] To improve the catalyst's activity and resistance to metal contamination, preferably, the magnesium content is 3-25 wt%, more preferably 5-20 wt%, based on the dry total weight of the magnesium-aluminum sol.

[0035] The magnesium content in the magnesium-aluminum sol described in this invention was determined by X-ray fluorescence (XRF).

[0036] The present invention does not have any particular limitation on the source of the magnesium-aluminum sol. It can be obtained commercially or by making it in-house, as long as it meets the above requirements for viscosity and magnesium content.

[0037] According to the present invention, preferably, based on the total weight of the catalyst, the content of the molecular sieve is 1-60% by weight, preferably 10-50% by weight; the content of the clay is 1-70% by weight, preferably 10-50% by weight; the content of the first binder is 1-25% by weight, preferably 5-20% by weight; the content of the second binder is 1-14% by weight, preferably 2-10% by weight; and the content of the third binder is 1-30% by weight, preferably 5-20% by weight.

[0038] The content of each component in the catalyst of the present invention is calculated by the feed ratio.

[0039] According to the present invention, preferably, the weight ratio of the first adhesive to the second adhesive is 1-5:1, more preferably 1-3:1.

[0040] According to the present invention, preferably, the weight ratio of the total weight of the first adhesive and the second adhesive to the weight of the third adhesive is 1-10:1, more preferably 1-6:1.

[0041] This invention, by rationally allocating three specific binders, helps to further improve the catalyst's resistance to metal contamination, while also further ensuring the catalyst's wear index.

[0042] The present invention allows for a wide range of molecular sieve types, which can be various molecular sieves commonly found in the art. Preferably, the molecular sieve is selected from at least one of Y molecular sieve, ZSM-5 molecular sieve, Beta molecular sieve, SAPO molecular sieve, and MCM molecular sieve.

[0043] Preferably, the Y molecular sieve is an ion-modified Y molecular sieve and / or an ultrastable Y molecular sieve.

[0044] Preferably, the ion modification includes at least one of rare earth ion modification, alkaline earth metal ion modification, transition metal ion modification, and phosphorus modification.

[0045] Preferably, the Y molecular sieve is selected from at least one of rare earth-containing Y molecular sieves, phosphorus-containing and rare earth-containing Y molecular sieves, ultrastable Y molecular sieves, and phosphorus-containing and / or rare earth-containing ultrastable Y molecular sieves.

[0046] More preferably, the Y molecule is screened from at least one of REHY molecular sieve, DOSY molecular sieve, and DASY molecular sieve.

[0047] The present invention allows for a wide range of clay types, and can use various existing clays suitable for use in catalytic cracking catalysts. For example, it can be selected from one or more of kaolin, montmorillonite, diatomaceous earth, soapstone, attapulgite, sepiolite, attapulgite, hydrotalcite, and bentonite. Preferably, the clay is selected from at least one of kaolin, montmorillonite, attapulgite, and bentonite.

[0048] The catalyst of this invention has a magnesium-rich shell, which coincides with the deposition location of contaminating metals on the catalyst surface (mainly enriched at 2-3 μm on the catalyst surface). This enhances the contact efficiency between the contaminating metals and the anti-metal component (magnesium-rich shell), giving the catalyst excellent resistance to metal contamination. According to this invention, preferably, the magnesium is distributed on the catalyst surface, and the thickness of the surface layer is 1-10 μm, more preferably 1-6 μm.

[0049] The catalyst surface layer described in this invention refers to the range of 1-10 μm from the surface of the catalyst particles inward.

[0050] The distribution of magnesium on the catalyst surface described in this invention was measured by EDS.

[0051] In the prior art, the wear index of catalysts is generally between 3-6%. The catalyst of the present invention has a lower wear index, which is beneficial to enhancing the catalyst's fluidization performance and high-temperature wear resistance, and is conducive to the catalyst's long life and long-term operation. Preferably, the wear index of the catalyst is not greater than 3%, and more preferably not greater than 1.5%.

[0052] A second aspect of the present invention provides a method for preparing a catalytic cracking catalyst, the method comprising the following steps:

[0053] (1) The first adhesive precursor is first sol-gelled;

[0054] (2) The material, molecular sieve and clay obtained in step (1) are mixed for the first time to obtain the first slurry, and then spray-dried for the first time to obtain the first microsphere particles with an average particle size of no more than 30 μm.

[0055] (3) The second adhesive precursor is subjected to a second sol-gel process;

[0056] (4) The material obtained in step (3), the first microsphere particles and the third binder precursor are mixed for the second time to obtain the second slurry, and then spray-dried for the second time to obtain the catalytic cracking catalyst.

[0057] Wherein, the first binder precursor is boehmite with a grain size of 2-5 nm, the second binder precursor is boehmite with a grain size of 10-30 nm, and the third binder precursor is magnesium aluminum sol with a viscosity of not less than 500 mPa·s.

[0058] According to the present invention, preferably, the first binder precursor is boehmite with a grain size of 2-5 nm, the second binder precursor is boehmite with a grain size of 10-20 nm, and the third binder precursor is magnesium aluminum sol with a viscosity of 500-2000 mPa·s.

[0059] The magnesium content in the magnesium-aluminum sol of the present invention is as described in the first aspect.

[0060] The present invention does not have any particular limitation on the source of the magnesium-aluminum sol. It can be obtained commercially or by making it in-house, as long as it meets the above requirements for viscosity and magnesium content.

[0061] According to the present invention, preferably, the amounts of the molecular sieve, clay, first binder precursor, second binder precursor, and third binder precursor are such that, based on the total weight of the catalyst, the content of the molecular sieve is 1-60% by weight, preferably 10-50% by weight; the content of the clay is 1-70% by weight, preferably 10-50% by weight; the content of the first binder is 1-25% by weight, preferably 5-20% by weight; the content of the second binder is 1-14% by weight, preferably 2-10% by weight; and the content of the third binder is 1-30% by weight, preferably 5-20% by weight.

[0062] According to the present invention, preferably, the weight ratio of the first binder precursor to the second binder precursor is 1-5:1, more preferably 1-3:1, wherein the first binder precursor and the second binder precursor are calculated as Al2O3.

[0063] According to the present invention, preferably, the total weight ratio of the first binder precursor and the second binder precursor to the dry basis weight ratio of the third binder precursor is 1-10:1, more preferably 1-6:1, wherein the first binder precursor and the second binder precursor are calculated as Al2O3.

[0064] According to the present invention, preferably, the viscosity of the material obtained in step (1) is not less than 20,000 mPa·s, and more preferably 20,000-50,000 mPa·s. This preferred embodiment is beneficial for reducing the catalyst attrition index.

[0065] According to the present invention, preferably, the viscosity of the material obtained in step (3) is not greater than 200 mPa·s, and more preferably 20-200 mPa·s. This preferred embodiment is more conducive to reducing the catalyst attrition index.

[0066] The viscosity described in this invention is measured using a viscometer.

[0067] The first and second sol-gel processes of this invention are conventional operations in the art and can be performed with reference to conventional methods in the art.

[0068] According to the present invention, preferably, the acid in the first colloidal solution and the acid in the second colloidal solution are each independently inorganic acids, preferably hydrochloric acid and / or nitric acid. These substances are all conventional choices in the art and are commercially available.

[0069] The present invention does not impose a particular limitation on the amount of acid used, and can be carried out with reference to conventional methods in the art. Preferably, the weight ratio of acid to boehmite (calculated as alumina) is 0.1-1:1.

[0070] According to the present invention, preferably, the average particle size in the first slurry is 2-8 μm. This preferred embodiment can further reduce the catalyst attrition index.

[0071] The average particle size in the first slurry of the present invention was obtained by measuring a laser particle size analyzer.

[0072] The present invention does not particularly limit the method for obtaining the particle size in the first slurry, and can refer to conventional methods in the art. The present invention will not elaborate further here.

[0073] According to the present invention, preferably, the solid content of the first slurry and the second slurry is each independently 20-35 wt%.

[0074] According to the present invention, preferably, the average particle size of the first microsphere is 20-30 μm.

[0075] The average particle size of the first microsphere in this invention was determined by a laser particle size analyzer.

[0076] According to the present invention, the temperature range for the first spray drying is relatively wide, and those skilled in the art can determine it based on the average particle size of the first microspheres. According to the present invention, preferably, the temperature for the first spray drying in step (2) is 250-350°C.

[0077] The present invention allows for a wide range of molecular sieve types, which can be various molecular sieves commonly found in the art. Preferably, the molecular sieve is selected from at least one of Y molecular sieve, ZSM-5 molecular sieve, Beta molecular sieve, SAPO molecular sieve, and MCM molecular sieve.

[0078] Preferably, the Y molecular sieve is an ion-modified Y molecular sieve and / or an ultrastable Y molecular sieve.

[0079] Preferably, the ion modification includes at least one of rare earth ion modification, alkaline earth metal ion modification, transition metal ion modification, and phosphorus modification.

[0080] Preferably, the Y molecular sieve is selected from at least one of rare earth-containing Y molecular sieves, phosphorus-containing and rare earth-containing Y molecular sieves, ultrastable Y molecular sieves, and phosphorus-containing and / or rare earth-containing ultrastable Y molecular sieves.

[0081] More preferably, the Y molecule is screened from at least one of REHY molecular sieve, DOSY molecular sieve, and DASY molecular sieve.

[0082] According to a preferred embodiment of the present invention, the molecular sieve is provided in the form of a first slurry, wherein the liquid medium in the first slurry is the same as the first liquid medium.

[0083] The present invention does not have any particular limitation on the amount of liquid medium used in the first slurry, but the solid content in the first slurry is within the above-mentioned range.

[0084] The present invention allows for a wide range of clay types, and can use various existing clays suitable for use in catalytic cracking catalysts. For example, it can be selected from one or more of kaolin, montmorillonite, diatomaceous earth, soapstone, attapulgite, sepiolite, attapulgite, hydrotalcite, and bentonite. Preferably, the clay is selected from at least one of kaolin, montmorillonite, attapulgite, and bentonite.

[0085] According to a preferred embodiment of the present invention, the clay is provided in the form of a second slurry, wherein the liquid medium in the second slurry is the same as that in the first liquid medium.

[0086] The present invention does not have any particular limitation on the amount of liquid medium used in the second slurry, but the solid content in the first slurry is within the above-mentioned range.

[0087] In this invention, the first mixing is carried out under stirring conditions. This invention does not particularly limit the stirring rate and time, as long as the goal of uniform mixing is achieved.

[0088] In the first mixing process of the material, molecular sieve, and clay obtained in step (1) of step (2), this invention does not impose any particular limitation on the order in which the materials are added. They can be added together or separately. This invention does not impose any limitation on this. In the embodiment of this invention, the order in which the material, clay, and molecular sieve obtained in step (1) are added is used as an example.

[0089] In the second mixing process of the material obtained in step (3), the first microsphere particles, and the third binder precursor, the present invention does not impose any particular limitation on the order of addition of the materials. They can be added together or separately. The present invention does not impose any limitation on this. In the embodiment of the present invention, the material obtained in step (3) is added first, followed by the first microsphere particles and the third binder precursor, as an example.

[0090] According to the present invention, preferably, the particle size of the particles in the second slurry is less than 8 μm, more preferably 90% of the particles are less than 6 μm, and more preferably 50% of the particles are less than 3 μm. Using this preferred embodiment, the catalyst attrition index can be further reduced.

[0091] The particle size of the second slurry in this invention is obtained by measuring a laser particle size analyzer.

[0092] The present invention does not particularly limit the method for obtaining the particle size in the second slurry, and can refer to conventional methods in the art. The present invention will not elaborate further here.

[0093] According to the present invention, the temperature range for the second spray drying is relatively wide and can be determined based on the average particle size of the second microspheres. Preferably, the temperature for the second spray drying in step (4) is 380-550°C.

[0094] According to the present invention, preferably, the method further includes: subjecting the first microsphere particles to a first calcination before subjecting the first microsphere particles to a second mixing.

[0095] The low-temperature calcination described in this invention is beneficial for the subsequent formation of the second particle and also helps to reduce the catalyst attrition index. Preferably, the conditions for the first calcination include: a temperature of 200-400℃, more preferably 200-350℃; and a time of 4-10 hours, more preferably 4-8 hours. The first calcination is generally carried out in an air atmosphere, which can include a flowing atmosphere or a stationary atmosphere.

[0096] According to the present invention, preferably, the method further includes: subjecting the second microsphere particles obtained by the second spray drying to a second calcination to obtain a catalytic cracking catalyst.

[0097] The second calcination conditions of this invention can be performed using conventional methods in the art. Preferably, the second calcination conditions include: a temperature of 400-800℃, more preferably 400-650℃; and a time of 1-12 hours, more preferably 1-8 hours. The second calcination is generally carried out in an air atmosphere, which may include a flowing atmosphere or a stationary atmosphere.

[0098] According to the present invention, preferably, the average particle size of the second microsphere is 30-120 μm, more preferably 40-100 μm.

[0099] The average particle size of the second microsphere in this invention was determined by a laser particle size analyzer.

[0100] According to the present invention, preferably, the method further includes: before performing a first solvation on the first adhesive precursor, first slurrying the first adhesive precursor with a first liquid medium to obtain a first suspension.

[0101] According to the present invention, preferably, the method further includes: before performing a second solvation on the second binder precursor, first slurrying the second binder precursor with a second liquid medium to obtain a second suspension.

[0102] According to the present invention, preferably, the solid content of the first suspension and the second suspension are each independently 10-35 wt%.

[0103] According to the present invention, preferably, the first liquid medium and the second liquid medium are each independently water and / or an organic solvent, preferably water.

[0104] In this invention, the terms "first" and "second" do not limit the substances and operations, but are only used to distinguish the substances introduced in different steps and the operations performed in different stages.

[0105] The third aspect of the present invention provides the application of the catalytic cracking catalyst described in the first aspect or the catalytic cracking catalyst prepared by the method described in the second aspect in the catalytic cracking of feedstock oil, preferably in the catalytic cracking of iron-containing feedstock oil, more preferably in the catalytic cracking of high-iron feedstock oil, wherein the iron content in the high-iron feedstock oil is 15-35 μg / g.

[0106] To better illustrate the anti-metal contamination performance of the catalyst described in this invention, the test examples of this invention use a catalyst impregnated with 5000 ppm iron to simulate a catalyst in actual applications where the contaminating metal elements reach equilibrium after long-term operation.

[0107] The present invention does not specifically limit the method for metal contamination, and the conventional methods of the present invention can be used. The present invention uses the Mitchell method as an example (Mitchell B R. Metal Contamination of Cracking Catalysts.1. Synthetic Metals Deposition on Fresh Catalysts[J].Industrial & Engineering Chemistry Product Research and Development,1980,19(2):209-213).

[0108] To test the stability of the catalyst, the metal-contaminated catalyst is subjected to an aging treatment before use. The present invention does not particularly limit the conditions of the aging treatment, and conventional methods in the art can be used.

[0109] The present invention will be described in detail below through embodiments.

[0110] DASY molecular sieve (92 wt% solid content, 1.8 wt% RE2O3, 1 wt% Na2O, 60% crystallinity), Beta molecular sieve (95.2 wt% solid content, 1.2 wt% Na2O, 60% crystallinity), and ZSM-5 molecular sieve (95 wt% solid content, 85% crystallinity) were all produced by Sinopec Catalyst Qilu Branch.

[0111] Both boehmite and magnesium aluminum sol are commercially available products from Zibo Zhonglida New Materials Co., Ltd.

[0112] Unless otherwise stated, all raw materials used in the following examples are commercially available products.

[0113] Example 1

[0114] The first binder precursor, boehmite, was mixed with deionized water to obtain a first suspension (15% by weight of solids). Hydrochloric acid was added to the first suspension to purge it, with an acid-to-alumina ratio (weight ratio of hydrochloric acid to boehmite based on alumina) of 0.2:1. A slurry containing kaolin (25% by weight of solids) was added to the purged material and stirred for 20 minutes. Then, DASY molecular sieve slurry (35% by weight of solids) was added, and stirring continued. The mixture was then sheared to obtain a first slurry (28% by weight of solids). The first slurry was then spray-dried to form first microspheres, which were then calcined.

[0115] A second suspension (15% by weight) was obtained by mixing and slurrying the second binder precursor, pseudoboehmite, with deionized water. Hydrochloric acid was added to the second suspension to form a gel, with an acid-to-alumina ratio (hydrochloric acid to pseudoboehmite by weight, calculated as alumina) of 0.2:1. Then, calcined first microspheres, the third binder precursor magnesium-aluminum sol, and deionized water were added. After shearing, a second slurry (28% by weight) was obtained. The particle size in the second slurry was less than 8 μm, with 90% of the particles less than 6 μm and 50% less than 3 μm. The second slurry was subjected to a second spray drying to produce second microspheres, which were then second-calcined to obtain the catalytic cracking catalyst C-1. The specific details of the viscosity of the first gelled material, the first spray drying temperature, the average particle size of the first particles, the first calcination conditions, the viscosity of the second gelled material, the second spray drying temperature, the average particle size of the second particles, and the second calcination conditions are listed in Table 1. The characteristic parameters of the catalyst are shown in Table 2.

[0116] An example is given of the EDS plot of the catalyst, such as... Figure 1 As shown, the magnesium is distributed on the surface of the catalyst at a depth of about 1-3 μm, which coincides with the deposition location of the contaminating metals on the catalyst surface. This enhances the contact efficiency between the contaminating metals and the anti-metal component (magnesium-rich shell), giving the catalyst excellent resistance to metal contamination.

[0117] Examples 2-5

[0118] Catalytic cracking catalysts C-2 to C-5 were prepared according to the method of Example 1, with the following differences: grain size of the first binder precursor, grain size of the second binder precursor, viscosity and magnesium content of the third binder precursor, viscosity of the first sol-gel material, average particle size of the particles in the first slurry, first spray drying temperature, average particle size of the first particles, first calcination conditions, viscosity of the second sol-gel material, second spray drying temperature, second average particle size, and second calcination conditions. Specific details of each example are listed in Table 1. Characteristic parameters of the catalysts are shown in Table 2.

[0119] Comparative Example 1

[0120] A suspension (15 wt% solids content) was obtained by mixing and slurrying the first and second binder precursors, pseudoboehmite, with deionized water. Hydrochloric acid sol was added to the suspension at an acid-to-alumina ratio (hydrochloric acid to pseudoboehmite weight based on alumina) of 0.2:1. Then, kaolin slurry (25 wt% solids content) was added and stirred for 20 minutes. Next, DASY molecular sieve slurry (35 wt% solids content) and the third binder precursor, magnesium aluminate sol, were added sequentially to obtain a slurry (28% solids content). The slurry was spray-dried at 400°C to produce catalyst particles with an average particle size of 60 μm, and then calcined at 500°C for 3 hours to obtain catalyst D-1. The viscosity, spray-drying temperature, average particle size, and calcination conditions of the sol-gel material are listed in Table 1. The characteristic parameters of the catalyst are shown in Table 2.

[0121] Magnesium is uniformly distributed within the catalyst, resulting in low contact efficiency between contaminating metals and the anti-metal component (magnesium), and the catalyst has poor resistance to metal contamination.

[0122] Comparative Example 2

[0123] The method of Example 1 was followed, except that boehmite with a grain size of 6 nm was used as the first binder precursor to obtain catalyst D-2. The specific details of the viscosity, first spray drying temperature, first average particle size, first calcination conditions, viscosity, second spray drying temperature, second average particle size, and second calcination conditions of the first sol-gel material are listed in Table 1. The characteristic parameters of the catalyst are shown in Table 2.

[0124] Magnesium is uniformly distributed within the catalyst, resulting in low contact efficiency between contaminating metals and the anti-metal component (magnesium), and the catalyst has poor resistance to metal contamination.

[0125]

[0126]

[0127] Test Example 1

[0128] The catalytic cracking catalysts prepared in the above examples and comparative examples were impregnated with 5000 ppm of contaminated iron using the Mitchell method. Specifically, an iron-containing solution was prepared using ferric naphthenate as the iron source and toluene as the solvent. The prepared catalyst was then impregnated in the iron-containing solution, dried, and calcined at 600°C. The catalysts were then aged at 780°C under 100% steam for 4 hours, and their cracking performance was evaluated in a small fixed fluidized bed reactor. The evaluation conditions for heavy oil micro-reaction were: a catalyst-to-feed oil mass ratio of 5, a catalyst loading of 9 g, a reaction temperature of 520°C, and a WHSV of 8 h for the feed oil. -1The oil inlet time was 70 seconds, and the feedstock was vacuum gas oil. The properties of the feedstock are shown in Table 3. The evaluation results are listed in Table 4.

[0129] Table 3

[0130]

[0131] Table 4

[0132]

[0133] Note: Conversion rate = Gasoline yield + Liquefied petroleum gas yield + Dry gas yield + Coke yield;

[0134] Total liquid product yield = gasoline yield + diesel yield + liquefied petroleum gas yield;

[0135] Coke selectivity = Coke yield / Conversion rate;

[0136] Dry gas selectivity = dry gas yield / conversion rate.

[0137] As can be seen from the results in Table 4, the catalyst prepared by the method provided in this invention has a high heavy oil conversion rate and a high total liquid product yield when used in heavy oil catalytic cracking.

[0138] Furthermore, the catalyst provided by this invention exhibits higher total liquid product yield and higher gasoline yield even under metal contamination conditions. This demonstrates that the catalyst provided by this invention possesses excellent resistance to metal contamination.

[0139] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.

Claims

1. A catalytic cracking catalyst, characterized in that, The catalyst comprises molecular sieves, clay, and composite binders; The composite binder includes a first binder, a second binder, and a third binder; the first binder is obtained by calcining boehmite with a grain size of 2-5 nm, the second binder is obtained by calcining boehmite with a grain size of 10-30 nm, and the third binder is obtained by calcining magnesium aluminum sol with a viscosity of not less than 500 mPa•s. Based on the dry total weight of the magnesium-aluminum sol, the magnesium content is 3-25 wt%; Based on the total weight of the catalyst, the content of the molecular sieve is 1-60% by weight; the content of the clay is 1-70% by weight; the content of the first binder is 1-25% by weight; the content of the second binder is 1-14% by weight; and the content of the third binder is 1-30% by weight. The magnesium is distributed on the surface of the catalyst, and the thickness of the surface layer is 1-6 μm.

2. The catalyst according to claim 1, wherein, The first binder is obtained by calcining boehmite with a grain size of 2-5 nm, the second binder is obtained by calcining boehmite with a grain size of 10-20 nm, and the third binder is obtained by calcining magnesium aluminum sol with a viscosity of 500-2000 mPa•s. Based on the dry total weight of the magnesium-aluminum sol, the magnesium content is 5-20 wt%.

3. The catalyst according to claim 1, wherein, Based on the total weight of the catalyst, the content of the molecular sieve is 10-50% by weight; the content of the clay is 10-50% by weight; the content of the first binder is 5-20% by weight; the content of the second binder is 2-10% by weight; and the content of the third binder is 5-20% by weight.

4. The catalyst according to claim 1, wherein, The weight ratio of the first adhesive to the second adhesive is 1-5:

1.

5. The catalyst according to claim 4, wherein, The weight ratio of the first adhesive to the second adhesive is 1-3:

1.

6. The catalyst according to claim 1, wherein, The total weight ratio of the first adhesive and the second adhesive to the weight ratio of the third adhesive is 1-10:

1.

7. The catalyst according to claim 6, wherein, The total weight ratio of the first adhesive and the second adhesive to the weight ratio of the third adhesive is 1-6:

1.

8. The catalyst according to any one of claims 1-7, wherein, The molecular sieve is selected from at least one of Y molecular sieve, ZSM-5 molecular sieve, Beta molecular sieve, SAPO molecular sieve and MCM molecular sieve; The clay is selected from at least one of kaolin, montmorillonite, attapulgite, and bentonite.

9. The catalyst according to any one of claims 1-7, wherein, The wear index of the catalyst is no greater than 3%.

10. The catalyst according to claim 9, wherein, The wear index of the catalyst is no greater than 1.5%.

11. A method for preparing a catalytic cracking catalyst, characterized in that, The method includes the following steps: (1) The first adhesive precursor is first sol-gelled; (2) The material, molecular sieve and clay obtained in step (1) are mixed for the first time to obtain the first slurry, and then spray-dried for the first time to obtain the first microsphere particles with an average particle size of no more than 30 μm. (3) The second adhesive precursor is subjected to a second sol-gel process; (4) The material obtained in step (3), the first microsphere particles and the third binder precursor are mixed for the second time to obtain the second slurry, and then spray-dried for the second time to obtain the catalytic cracking catalyst; Wherein, the first binder precursor is boehmite with a grain size of 2-5 nm, the second binder precursor is boehmite with a grain size of 10-30 nm, and the third binder precursor is magnesium aluminum sol with a viscosity of not less than 500 mPa•s. The magnesium content is 3-25 wt%, based on the dry total weight of the magnesium-aluminum sol. The amounts of the molecular sieve, clay, first binder precursor, second binder precursor, and third binder precursor are such that, based on the total weight of the catalyst, the content of the molecular sieve is 1-60% by weight; the content of the clay is 1-70% by weight; the content of the first binder is 1-25% by weight; the content of the second binder is 1-14% by weight; and the content of the third binder is 1-30% by weight. The magnesium is distributed on the surface of the catalyst, and the thickness of the surface layer is 1-6 μm.

12. The method according to claim 11, wherein, The first binder precursor is boehmite with a grain size of 2-5 nm, the second binder precursor is boehmite with a grain size of 10-20 nm, and the third binder precursor is magnesium aluminum sol with a viscosity of 500-2000 mPa•s. Based on the dry total weight of the magnesium-aluminum sol, the magnesium content is 5-20 wt%.

13. The method according to claim 11, wherein, The amounts of the molecular sieve, clay, first binder precursor, second binder precursor, and third binder precursor are such that, based on the total weight of the catalyst, the content of the molecular sieve is 10-50% by weight; the content of the clay is 10-50% by weight; the content of the first binder is 5-20% by weight; the content of the second binder is 2-10% by weight; and the content of the third binder is 5-20% by weight.

14. The method according to claim 11, wherein, The weight ratio of the first binder precursor to the second binder precursor is 1-5:1, wherein the first binder precursor and the second binder precursor are calculated as Al2O3.

15. The method according to claim 14, wherein, The weight ratio of the first binder precursor to the second binder precursor is 1-3:1, wherein the first binder precursor and the second binder precursor are calculated as Al2O3.

16. The method according to claim 11, wherein, The total weight ratio of the first and second binder precursors to the dry basis weight ratio of the third binder precursor is 1-10:1, wherein the first and second binder precursors are calculated as Al2O3.

17. The method according to claim 16, wherein, The total weight ratio of the first and second binder precursors to the dry basis weight ratio of the third binder precursor is 1-6:1, wherein the first and second binder precursors are calculated as Al2O3.

18. The method according to any one of claims 11-17, wherein, The viscosity of the material obtained in step (1) is not less than 20000 mPa•s.

19. The method according to claim 18, wherein, The viscosity of the material obtained in step (1) is 20,000-50,000 mPa•s.

20. The method according to any one of claims 11-17, wherein, The viscosity of the material obtained in step (3) is no greater than 200 mPa•s.

21. The method according to claim 20, wherein, The viscosity of the material obtained in step (3) is 20-200 mPa•s.

22. The method according to any one of claims 11-17, wherein, The acids in the first and second colloids are each independently inorganic acids.

23. The method according to claim 22, wherein, The acids in the first and second colloids are each independently hydrochloric acid and / or nitric acid.

24. The method according to any one of claims 11-17, wherein, The average particle size in the first slurry is 2-8 μm.

25. The method according to any one of claims 11-17, wherein, The solid content of the first slurry and the second slurry is independently 20-35 wt%.

26. The method according to any one of claims 11-17, wherein, The average particle size of the first microsphere is 20-30 μm.

27. The method according to any one of claims 11-17, wherein, Step (2) The temperature of the first spray drying is 250-350℃.

28. The method according to any one of claims 11-17, wherein, The molecular sieve is selected from at least one of Y molecular sieve, ZSM-5 molecular sieve, Beta molecular sieve, SAPO molecular sieve and MCM molecular sieve; The clay is selected from at least one of kaolin, montmorillonite, attapulgite, and bentonite.

29. The method according to any one of claims 11-17, wherein, The particle size in the second slurry is less than 8 μm.

30. The method according to claim 29, wherein, In the second slurry, 90% of the particles have a diameter of less than 6μm.

31. The method according to claim 30, wherein, In the second slurry, 50% of the particles have a diameter of less than 3μm.

32. The method according to any one of claims 11-17, wherein, In step (4), the temperature of the second spray drying is 380-550℃.

33. The method according to any one of claims 11-17, wherein, The method further includes: subjecting the first microsphere particles to a first calcination before the second mixing of the first microsphere particles; The conditions for the first roasting include: a temperature of 200-400℃ and a time of 4-10h.

34. The method according to claim 33, wherein, The conditions for the first roasting include: a temperature of 200-350℃ and a time of 4-8 hours.

35. The method according to any one of claims 11-17, wherein, The method further includes: subjecting the second microsphere particles obtained by the second spray drying to a second calcination to obtain a catalytic cracking catalyst; The conditions for the second roasting include: a temperature of 400-800℃ and a time of 1-12h.

36. The method according to claim 35, wherein, The conditions for the second roasting include: a temperature of 400-650℃ and a time of 1-8 hours.

37. The method of claim 35, wherein, The average particle size of the second microsphere is 30-120 μm.

38. The method according to claim 37, wherein, The average particle size of the second microsphere is 40-100 μm.

39. The method according to any one of claims 11-17, wherein, The method further includes: before performing a first solvation on the first adhesive precursor, first slurrying the first adhesive precursor with a first liquid medium to obtain a first suspension; The method further includes: before the second adhesive precursor is slurried with a second liquid medium to obtain a second suspension; The solid content of the first suspension and the second suspension is independently 10-35 wt%; The first liquid medium and the second liquid medium are each independently water and / or an organic solvent.

40. The use of a catalytic cracking catalyst according to any one of claims 1-10 or a catalytic cracking catalyst prepared by any one of claims 11-39 in the catalytic cracking of feedstock oil.

41. The application according to claim 40, wherein, Application of the catalytic cracking catalyst in the catalytic cracking of iron-containing feedstock oil.

42. The application according to claim 41, wherein, The application of the catalytic cracking catalyst in the catalytic cracking of high-iron feedstock oil, wherein the iron content of the high-iron feedstock oil is 15-35 μg / g.

Citation Information

Patent Citations

  • Catalytic cracking catalyst capable of resisting heavy metal pollution as well as preparation method and application of catalytic cracking catalyst

    CN113492014A

  • Heavy metal-resistant matrix-type cracking catalyst and its preparing process

    CN1334315A

  • Process for the cracking of high metals content feedstocks

    US3944482A

  • Vanadium passivation in a hydrocarbon catalytic cracking process

    US4750988A

  • SCR (Selective Catalytic Reduction) denitration catalyst and preparation method thereof

    CN103007923A